Target Hopping as a Useful Tool for the Identification of Novel EphA2 Protein–Protein Antagonists. Issue 1 (20th September 2013) - Tognolini, Massimiliano; Incerti, Matteo; Pala, Daniele; Russo, Simonetta; Castelli, Riccardo; Hassan‐Mohamed, Iftiin; Giorgio, Carmine; Lodola, Alessio
Abstract Lithocholic acid (LCA), a physiological ligand for the nuclear receptor FXR and the G‐protein‐coupled receptor TGR5, has been recently described as an antagonist of the EphA2 receptor, a key member of the ephrin signalling system involved in tumour growth. Given the ability of LCA to recognize FXR, TGR5, and EphA2 receptors, we hypothesized that the structural requirements for a small molecule to bind each of these receptors might be similar. We therefore selected a set of commercially available FXR or TGR5 ligands and tested them for their ability to inhibit EphA2 by targeting the EphA2‐ephrin‐A1 interface. Among the selected compounds, the stilbene carboxylic acid GW4064 was identified as an effective antagonist of EphA2, being able to block EphA2 activation in prostate carcinoma cells, in the micromolar range. This finding proposes the "target hopping" approach as a new effective strategy to discover new protein–protein interaction inhibitors.